Management of Bandhyatava (Infertility) by Sodhan Followed by Shaman Chikitsa: A Case Report (International Journal of Ayurveda and Pharma Research, 2021)
As per Ayurveda Vandhyatva occurs due to the vitiation of Vata Dosha which affects basic four constituents of Garbha sthapana. In modern science Infertility is described as an inability to conceive despite unprotected sex for duration of one year or more and PCOS is a major causative factor behind it. PCOS results in deterioration of female reproductive health which leads to infertility. In Ayurveda Samhithas, vast range of treatment methods are described. The basic aim in Ayurveda is to correct Ritu, Kshetra, Ambu and Beeja, the four basic factors for infertility by Shamana and Shodhan Chikitsa. Panchkarma provides best efficacy because it helps in balancing Doshas and Dushyas. Uttarbasti is also indicated for infertility which helps in detoxification of reproductive tract and balancing Vata Dosha, finally helps in retaining Garbha. In this case report importance of Sodhan Chikitsa before Shaman Chikitsa in case of infertility is emphasized.